1996
DOI: 10.1111/j.1365-2869.1996.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of auditory stimuli during tonic and phasic periods of REM sleep as revealed by event‐related brain potentials

Abstract: SUMMARY The brain has been reported to be more preoccupied with dreams during phasic than during tonic REM sleep. Whether these periods also differ in terms of the processing of external stimuli was examined. Event-related brain potentials (ERPs) to a frequent standard tone of 1000 Hz (P =97%) and infrequent deviant tones of 1100 and 2000 Hz (P= 1.S% f o r each) were recorded (n = 13) during wakefulness and nocturnal sleep.An ERP wave (called REM-P3) resembling a waking P3 wave was larger for the 2000 Hz devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 22 publications
(12 reference statements)
8
63
1
Order By: Relevance
“…To reconcile these observations, it is worth noting that the memory effect was positively associated with the proportion of tREM, and thus negatively correlated with the proportion of pREM. This result is in line with previous findings of increased sensitivity to sensory information in tREM 39, 48 . Interestingly, dream reports seem more vivid in pREM 49 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To reconcile these observations, it is worth noting that the memory effect was positively associated with the proportion of tREM, and thus negatively correlated with the proportion of pREM. This result is in line with previous findings of increased sensitivity to sensory information in tREM 39, 48 . Interestingly, dream reports seem more vivid in pREM 49 .…”
Section: Discussionsupporting
confidence: 93%
“…However, these broadly defined phases contain a number of distinct events: REM sleep is composed of a tonic and a phasic subphase, defined by the respective absence or presence of rapid eye movements; tonic (tREM) and phasic (pREM) REM sleep have been shown to differentially impact sensory processing 39, 40 ; NREM sleep contains sleep spindles and slow waves 41 , which are assumed to gate sensory processing 42 and organize memory consolidation 12, 13 . To better understand the neural events that led to plasticity during sleep, we correlated behavioral and EEG data with these various sleep markers.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that relatively complex differential processing of acoustic information continues during paradoxical sleep, as evidenced by the presence of event-related potential components P300 (Cote & Campbell 1999a, 1999bPerrin, Garcia-Larrea, Mauguiere, & Bastuji, 1999;Sallinen, Kaartinen, & Lyytinen, 1996) and mismatch negativity (Atienza, Cantero, & Gomez, 2000;Loewy, Campbell, & Bastien, 1996;Loewy, Campbell, de Lugt, Elton, & Kok, 2000;Nashida et al, 2000). The present study demonstrates that impairment of differential acoustic processing, as measured by P50 sensory gating, can also be expressed during this particular state.…”
Section: Resultsmentioning
confidence: 51%
“…1, to substitute the term 'midi'-bursts for what we used to call 'network bursts' of spike activity (e.g., Corner et al, 2002Corner et al, , 2005Corner and Crain, 1965;Habets et al, 1987;Ramakers et al, 1990Ramakers et al, , 1991. [The in situ equivalent to these in vitro 'midi-bursts' is phasic discharges, a term that has often been used (e.g., Corner, 1977Corner, , 1990Jouvet, 1972;Kohyama, 1996;Orem, 1996) to describe spontaneous events lasting on the order of a few seconds, in particular those occurring during episodes of rapid-eye-movement sleep (also see Sallinen et al, 1996;Takahara et al, 2002;Wehrle et al, 2007). ]…”
Section: Theoretical and Methodological Backgroundmentioning
confidence: 99%